A prodrug micellar carrier assembled from polymers with pendant farnesyl thiosalicylic acid moieties for improved delivery of paclitaxel. (1st October 2016) - Sun, Jingjing; Chen, Yichao; Li, Ke; Huang, Yixian; Fu, Xiaofeng; Zhang, Xiaolan; Zhao, Wenchen; Wei, Yuan; Xu, Liang; Zhang, Peijun; Venkataramanan, Raman; Li, Song
Graphical abstract: Abstract: In order to achieve enhanced and synergistic delivery of paclitaxel (PTX), a hydrophobic anticancer agent, two novel prodrug copolymers, POEG15 - b -PFTS6 and POEG15 - b -PFTS16 composed of hydrophilic poly(oligo(ethylene glycol) methacrylate) (POEG) and hydrophobic farnesylthiosalicylate (FTS, a nontoxic Ras antagonist) blocks, were synthesized. Both POEG- b -PFTS polymers were able to form micelles with intrinsic antitumor activity in vitro and in vivo . Employing these micelles as a carrier to load PTX, their drug loading capacity, stability, in vivo biodistribution and tumor inhibition effect were evaluated. PTX/POEG15 - b -PFTS16 mixed micelles exhibited an excellent stability of 9 days at 4 °C with a PTX loading capacity of 8.2%, which was more effective than PTX/POEG15 - b -PFTS6 mixed micelles. In vivo biodistribution data showed that DiR-loaded POEG- b -PFTS micelles were more effectively localized in the tumor than in other organs. Moreover, both PTX/POEG- b -PFTS micelles showed significantly higher antitumor activity than Taxol in a 4T1.2 murine breast tumor model, and the tumor inhibition and animal survival followed the order of PTX/POEG15 - b -PFTS16 > PTX/POEG15 - b -PFTS6 > POEG15 - b -PFTS16 > Taxol ≈ POEG15 - b -PFTS6 . Our data suggest that POEG- b -PFTS micelles are a promising anticancer drug carrier that warrants more studies in the future. Statement of Significance: Polymerization of drug-based monomer represents a facile and precise method to obtain well-defined polymeric prodrug amphiphiles. Currently, most reports largely focus on the synthesis methods and the biophysical properties. There is limited information about their anti-tumor activity and delivery function as prodrug carriers in vitro and in vivo . In this manuscript, we report the development of two novel prodrug copolymers, POEG15- b -PFTS6 and POEG15- b -PFTS16 composed of hydrophilic poly(oligo(ethylene glycol) methacrylate) (POEG) and hydrophobic farnesylthiosalicylate (FTS, a nontoxic Ras antagonist) blocks. Both POEG- b -PFTS polymers were able to self-assemble into nano-sized micelles with intrinsic antitumor activity in vitro and in vivo . More importantly, POEG- b -PFTS polymers were effective in forming stable mixed micelles with various anticancer agents including PTX, DOX, docetaxel, gefitinib, and imatinib. Delivery of PTX via our new carrier led to significantly improved antitumor activity, suggesting effective PTX/FTS combination therapy. We believe that our study shall be of broad interest to the readers in the fields of biomaterials and drug delivery.